IL-1α mediates cellular cross-talk in the airway epithelial mesenchymal trophic unit. Issue 3 (2nd July 2016) - Hill, Alison R.; Donaldson, Jessica E.; Blume, Cornelia; Smithers, Natalie; Tezera, Liku; Tariq, Kamran; Dennison, Patrick; Rupani, Hitasha; Edwards, Matthew J.; Howarth, Peter H.; Grainge, Christopher; Davies, Donna E.; et al.
ABSTRACT: The bronchial epithelium and underlying fibroblasts form an epithelial mesenchymal trophic unit (EMTU) which controls the airway microenvironment. We hypothesized that cell-cell communication within the EMTU propagates and amplifies the innate immune response to respiratory viral infections. EMTU co-culture models incorporating polarized (16HBE14o-) or differentiated primary human bronchial epithelial cells (HBECs) and fibroblasts were challenged with double-stranded RNA (dsRNA) or rhinovirus. In the polarized EMTU model, dsRNA affected ionic but not macromolecular permeability or cell viability. Compared with epithelial monocultures, dsRNA-stimulated pro-inflammatory mediator release was synergistically enhanced in the basolateral compartment of the EMTU model, with the exception of IL-1α which was unaffected by the presence of fibroblasts. Blockade of IL-1 signaling with IL-1 receptor antagonist (IL-1Ra) completely abrogated dsRNA-induced basolateral release of mediators except CXCL10. Fibroblasts were the main responders to epithelial-derived IL-1 since exogenous IL-1α induced pro-inflammatory mediator release from fibroblast but not epithelial monocultures. Our findings were confirmed in a differentiated EMTU model where rhinovirus infection of primary HBECs and fibroblasts resulted in synergistic induction of basolateral IL-6 that was significantly abrogated by IL-1Ra. This study provides the first direct evidence of integrated IL-1 signaling within the EMTU to propagate inflammatory responses to viral infection.